Penggunaan Modul Pembelajaran Dalam Meningkatkan Kemampuan Menterjemahkan Ayat Al-Qur’an Pada Program Tahfiz Al-Qur’an Siswa Kelas VII MTs Swasta Teladan Gebang - Siska Harianti, Kamaliah, Khairuddin (Education Achievement: Journal of Science and Research, 2022)
The availability of Learning Modules that contain a special program for Tahfizul Qur'an will certainly greatly assist teachers in delivering material and make it easier for students to improve their ability to translate the Qur'an due to the implementation of Learning Modules that are competency-based in translating the Qur'an according to the Tahfizul Qur'an program. contained in the Learning Module. The problem to be studied is a problem that has high urgency so that it is urgent to solve and find a solution considering the availability of time and costs as well as other supporting resources in carrying out this research is very minimal. So, the researcher determines the research model to be carried out, namely the class action research model (CAR). The results of this study are that learning modules can improve students' ability to translate verses in the Al-Qur'an Hadith subject for class VII students of MTs Teladan Gebang with a percentage increase, namely from the pre-cycle completeness score of at least only 56.55% of students. Then in the first cycle, the percentage of completeness was achieved at 63.64%, an increase of 7.8% from the pre-cycle. In cycle II, the percentage of learning completeness was 78.8%, there was another increase of 15% from cycle I. In cycle III, learning mastery was achieved by 90.3%, an increase from cycle II. So from pre cycle to cycle III there is an increase in level of 33.7%. The percentage is obtained from the scores of students who have fulfilled the Minimum Mastery Criteria (KKM), which is 70 for Al-Qur'an Hadith subjects. The value of completeness achievement in understanding the material Translating verses of the Qur'an by students as an indicator of the level of achievement of learning achievement. Individual student scores are also increasing. Therefore it can be concluded that the application of learning modules can be a solution in improving students' ability to translate verses of the Qur'an.